Prevalence and risk factors of overweight and obesity among MBBS students - Baruah, Chetanjit; Gupta, Kajal; Luthra, Megha (International Journal Of Community Medicine And Public Health, 2020)
Background: Obesity is a life style disease. During college years students living away from home, are faced with many different food choices. So, this study was done to determine the prevalence of overweight and obesity and its risk factors among MBBS students. Methods: A cross sectional study was conducted among 318 MBBS students of Gauhati Medical College and Hospital, Assam from June to July 2017 by purposive sampling using a pre-designed, semi-structured questionnaire. Results: Prevalence of overweight and obesity was found to be 16.7% and 2.5% and higher among students who were non-vegetaranian, had irregular dietary habit, consume junk foods and carbonated drinks, used Motorized vehicle as a mode of transport, sleep >8 hrs per day and had family history of obesity, hypertension, diabetes mellitus and heart disease. Conclusions: There is need to increase awareness among the students in order to reduce the future burden of obesity associated chronic diseases.